Geriatric nutritional risk index as a predictor of prognosis in hematologic malignancies: a systematic review and meta-analysis - Yu, Qiong; Tian, Mengxing; Pi, Guoliang; Jia, Yegui; Jin, Xin (Frontiers in Nutrition, 2023)
Recent studies have reported inconsistent results regarding the association between geriatric nutritional risk index (GNRI) and clinical outcomes in patients with hematologic malignancies (HMs). We performed a meta-analysis to evaluate the effect of low GNRI on the overall survival (OS) and progression-free survival (PFS) in patients with HMs.We conducted the research via PubMed, Embase, and Cochrane Library databases to identify trials. exploring the association between GNRI and prognosis in patients with HMs. A meta-analysis of OS and PFS was performed. Quality In Prognostic Studies instrument and Newcastle-Ottawa quality assessment Scale were used to assess the quality of included trials.2 This is a provisional file, not the final typeset article Fourteen studies enrolling 3524 patients with HMs were included. Low GNRI was associated with shorter OS (Hazard ratio (HR) = 1.77; 95% CI = 1.44 -2.18, p < 0.01) and PFS (HR = 1.63; 95% CI = 1.17 -2.27, p < 0.01) in patients with HMs. In the subgroup analysis, GNRI was not significantly associated with prognosis in Chinese patients with HMs (OS, HR =1.33; 95% CI = 0.89 -1.98, p = 0.16; PFS, HR = 1.70; 95% CI = 0.72 -4.01, p= 0.23). For the subgroup with a GNRI cutoff value less than 98, there was no significant difference in PFS (HR = 1.34; 95% CI = 0.98 -1.83, p= 0.06).Low GNRI negatively impacted on the prognosis in patients with HMs. Prospective studies to identify the best cut-off value for GNRI are required.